The Role of Thromboxane in the Course and Treatment of Ischemic Stroke: Review - Małgorzata Szczuko (MDPI AG, 2021)
Cardiovascular diseases are currently among the leading causes of morbidity and mortality in many developed countries. They are distinguished by chronic and latent development, a course with stages of worsening of symptoms and a period of improvement, and a constant potential threat to life. One of the most important disorders in cardiovascular disease is ischemic stroke. The causes of ischemic stroke can be divided into non-modifiable and modifiable causes. One treatment modality from a neurological point of view is acetylsalicylic acid (ASA), which blocks cyclooxygenase and, thus, thromboxane synthesis. The legitimacy of its administration does not raise any doubts in the case of the acute phase of stroke in patients in whom thrombolytic treatment cannot be initiated. The measurement of thromboxane B2 (TxB2) in serum (a stable metabolic product of TxA2) is the only test that measures the effect of aspirin on the activity of COX-1 in platelets. Measurement of thromboxane B2 may be a potential biomarker of vascular disease risk in patients treated with aspirin. The aim of this study is to present the role of thromboxane B2 in ischemic stroke and to present effective therapies for the treatment of ischemic stroke. Scientific articles from the PubMed database were used for the work, which were selected on the basis of a search for “thromboxane and stroke”. Subsequently, a restriction was introduced for works older than 10 years, those concerning animals, and those without full text access. Ultimately, 58 articles were selected. It was shown that a high concentration of TXB2 may be a risk factor for ischemic stroke or ischemic heart disease. However, there is insufficient evidence to suggest that thromboxane could be used in clinical practice as a marker of ischemic stroke. The inclusion of ASA in the prevention of stroke has a beneficial effect that is associated with the effect on thromboxane. However, its insufficient power in 25% or even 50% of the population should be taken into account. An alternative and/or additional therapy could be a selective antagonist of the thromboxane receptor. Thromboxane A2 production is inhibited by estrogen; therefore, the risk of CVD after the menopause and among men is higher. More research is needed in this area.